The Study of The Impact of Onshore Harbor Layout on Coastal Sedimentation and Erosion at Pekalongan Beach - Fattah, Zihad Al; Sangkawati, Sri; Suharyanto, Suharyanto (Universitas Negeri Semarang, 2023)
Pekalongan City is an area that frequently experiences floods. In response, the government has launched a flood management program for the Pekalongan area, which includes the relocation of the National Fishery Harbor Pekalongan. The construction of the Pekalongan Onshore Harbor will change marine hydrodynamics, current, waves and sediments. To address these issues, it is necessary to conduct a study of these changes. According to the modeling results, the maximum current speed in the harbor pool ranges from 0 to 0.28 m/s, while the maximum wave height in the harbor pool falls within the range of 0 to 0.40 meters. The bed level change at the end of modeling in the harbor pool is 0.108 mm. Notably, the construction of the Pekalongan Onshore Harbor, as per the planned layout, induces hydrodynamic changes. An indicator of a hydrodynamics change is the alteration in currents at T4 and T5 in each model. In the proposed harbor layout, T4 and T5 exhibit a decrease in current speed, while the wave height remains relatively consistent. This change reduces erosion at T5 and even leads to sedimentation at T4 within the planned harbor layout.